Effect of sorghum dried distillers grains with solubles on composition, retail stability, and sensory attributes of ground pork from barrows and gilts - G R Skaar; Terry A Houser; K M Sotak; B L Goehring; A Stickel; B M Gerlach; K Steele; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 2011)
A total of 288 finishing pigs (PIC TR4 × 1050, initially 129.6 lb) were utilized as part of a 73-d feeding study to determine the effects of sorghum dried distillers grains with solubles (S-DDGS) in sorghum- or corn-based diets on ground pork quality. The dietary treatments included sorghum-based diets with 0, 15, 30, or 45% S-DDGS, a sorghum-based diet with 30% corn DDGS (C-DDGS), and a corn-based diet with 30% C-DDGS. Shoulders from 24 barrow and 24 gilt carcasses were ground, packaged, and evaluated for proximate and fatty acid composition, iodine value (IV), objective color and oxidation shelf-life, and sensory attributes. Finishing diet and gender did not interact to affect composition, fatty acid profile, color, or oxidative rancidity (P>0.05). Pork from gilts contained less fat and more moisture (P<0.001), was less saturated with a greater IV and total percentage of polyunsaturated fatty acids (P<0.01), and was also darker (P<0.001) and more red (P = 0.004) than pork from barrows. Gender did not affect (P>0.05) total color change from 0 to 120 h, oxidative rancidity, or sensory attributes of ground pork. Finishing diet had no effect on total fat, moisture, or protein composition. Increasing S-DDGS resulted in a linear (P<0.001) decrease in saturated and monounsaturated fatty acids (MUFA) and an increase (P<0.01) in polyunsaturated fatty acids (PUFA) and pork IV. Pork from pigs fed 30% S-DDGS had a greater percentage of MUFA, a lower percentage of PUFA, and reduced IV compared with pork from pigs fed 30% C-DDGS. Diet did not affect oxidative rancidity (P = 0.37) or objective color CIE L* (brightness), a* (redness), or b* (yellowness) values (P â‰¥ 0.09), but was shown to influence total color change (P = 0.01), with pork from pigs fed sorghum grain and 30% S-DDGS showing less total change than all other dietary treatments. All pork products were characterized with similar sensory descriptors. Overall, increasing S-DDGS during finishing resulted in ground pork with a more unsaturated fatty acid profile. Utilization of S-DDGS compared with an equal level of C-DDGS resulted in pork with a more saturated fatty acid profile and reduced IV; however, product differences were not carried through to alter oxidative rancidity or sensory attributes.; Swine Day, Manhattan, KS, November 17, 2011
Keywords: Swine Day; 2011; Kansas Agricultural Experiment Station contribution; no. 12-064-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1056; Swine; DDGS; Gender; Pork quality; Sensory attributes; Sorghum